Making a Saw Sam Sai Solo Phleng Dok Mai Sai - Jaroenchinwoot, Boondarika; Seemuang , Jatuporn (Journal of Fine and Applied Arts Khon Kaen University, 2020)
Dok Mai Sai is the one song that is played in lullaby, due to the melodious and popular melodies. The original chapter has both the male and female chapters in Doksoysawan. It is form of flirtation between a man and a woman is only the lyrics that aren’t recorded. The author brought Dok Mai Sai three fold both of the melody and the vocals and the instrument music of Phrayaprasandooriyasub’ s original in analysis and making a saw sam sai solo a variation on Phleng Dok Mai Sai sam chan. Which includes two melodic lines is melisma and pecia. In the melodies there are form in thai musical called “Ode Phan”, which the melodious songs must be played in the style of “Ode Phan” in order to enjoy the listening and the sound of the instrument music is only five sounds which are divided into groups called “Panjakosa”. The song Dok Mai Sai is a melodious song and is Thai song that should be learned.